ANALISIS VISUAL PADA FILM ANIMASI ADIT SOPO JARWO EPISODE EYANG HABIBIE - Ranny Vendra Kasyih; Iwan Muhammad Ridwan (Jurnal Digital Media dan Relationship, 2022)
Film is one form of mass media communication in an effort to convey messages. Mass communication has very important provisions, namely communicators, media, information, public, and reciprocity is the response of the recipient of the message, namely the public to the communicator. The progress of animated films from year to year is not a fairly instant process. the purpose of this study was to reveal visual signs, meanings, and messages. The researcher used Charles Sanders Peirce's semiotic analysis method. Peirce's semiotic method is known as the triadic model, namely Sign, Object, and Interpretant. With the semiotic analysis method of Charles Sanders Peirce in this study to facilitate analysis. In this study, the researcher succeeded in suggesting the signs, meanings, and messages contained in the animated film Adit and Sopo Jarwo Episode Eyang Habibie. The researcher concluded that this film is an example entertainment films that are suitable for both viewing and learning. From the descriptions and analyzes that have been described in previous chapters, the films shown have elements of Indonesian culture, Indonesian people's lives, and many messages contained in each show.